2018
DOI: 10.1080/13561820.2018.1470497
|View full text |Cite
|
Sign up to set email alerts
|

Learning from students: Facilitators’ learning in interprofessional placements

Abstract: Few studies have examined experiences and learning from the viewpoint of interprofessional facilitators of student placements, and limited research has investigated this learning enacted across traditional service boundaries or between health and education practitioners. This study aimed to address these gaps by exploring perceptions about the learning and experiences of Early Childhood Educators (ECEs) who facilitated placements in childcare settings for speech-language pathology students from a health profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…The supervisors who participated in the home visits and seminars also reported that they found the activity to be rewarding, and some even expressed that they had learned from students and supervisors from other professions. This is in line with a study by Attrill, Brebner and Marsh (2018) where facilitators for interprofessional clinical placements perceived that they learned from working together with students.…”
Section: Discussionsupporting
confidence: 89%
“…The supervisors who participated in the home visits and seminars also reported that they found the activity to be rewarding, and some even expressed that they had learned from students and supervisors from other professions. This is in line with a study by Attrill, Brebner and Marsh (2018) where facilitators for interprofessional clinical placements perceived that they learned from working together with students.…”
Section: Discussionsupporting
confidence: 89%